2005
DOI: 10.1111/j.1742-7843.2005.pto_160.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Effects of Intravenous Bisphosphonates in the Rat

Abstract: Bisphosphonates are potent osteoclast inhibitors that have been associated with renal toxicity following rapid intravenous administration of high doses, which was hypothesised to be due to precipitation of bisphosphonate aggregates or complexes in the kidney. Five studies were conducted in rats investigating the characteristics of bisphosphonate-related acute renal effects. These studies included single intravenous injections of the nitrogen-containing bisphosphonates (1) ibandronate (1-20 mg/kg), or (2) zoled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Preclinical studies have shown significant differences in renal toxicity between agents, possibly related to different degrees of accumulation and retention in the kidney [26,27]. In clinical trials of intravenous ibandronate, the renal safety profile has consistently been shown to be similar to placebo, even after long-term treatment [3,5].…”
Section: Introductionmentioning
confidence: 97%
“…Preclinical studies have shown significant differences in renal toxicity between agents, possibly related to different degrees of accumulation and retention in the kidney [26,27]. In clinical trials of intravenous ibandronate, the renal safety profile has consistently been shown to be similar to placebo, even after long-term treatment [3,5].…”
Section: Introductionmentioning
confidence: 97%
“…[15,21] However, no corpuscular precipitations were reported during kidney histopathological analysis in animals. [22][23][24][25][26][27][28] Therefore, it has been postulated that bisphosphonates induce cell death in renal cells in a manner similar to their apoptotic effects in osteoclasts and possibly even cancer cells. [24,25] Although oral treatment with bisphosphonates in cancer treatment has been available for many years, clinical experience has indicated that it was less effective than intravenous bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…It is effective in the treatment of hypercalcemia and bone metastasis, and widely used for various malignancies (2). However, it has been reported to be nephrotoxic (3)(4)(5), and several cases of acute tubular necrosis due to zoledronic acid have been reported (3). We encountered a breast cancer patient who developed Fanconi syndrome due to zoledronic acid.…”
Section: Introductionmentioning
confidence: 99%